(untitled) (Bangladesh Journal of Botany, 2021)
Effects of bio-organic fertilizer to organic carbon (SOC), dissolved organic carbon (DOC), easy oxidation of organic carbon (ROC), microbial biomass carbon (MBC) and Shamrock biomass were studied. The results showed that the contents of SOC, DOC, ROC, MBC could be significantly increased by bioorganic fertilizer. When cultured for 180d, SOC and DOC increased by 42 154 and 9 40%, respectively, compared with T0 treatment. ROC and MBC content increased by 38 173 and 4 9%, respectively. In addition, with the increase of the application of bio-organic fertilizer, the SOC and DOC contents increased. In T4 treatment, the SOC and DOC contents were the highest, which were 25.05 g/kg and 74.89 mg/kg, respectively. In T3 treatment, the ROC and MBC contents were the highest, 9.84 g/kg and 167.09 mg/kg, respectively. Compared with the initial incubation period, SOC decreased by 6 17%, DOC increased by 3 13%, ROC and MBC increased by 15 64, 3 25%, respectively. The application of bio-organic fertilizer increased the aboveground and underground biomass and the highest value were in the T2 and T3 treatments, respectively. The application of biological organic fertilizer increased the content of active organic carbon components. Results of the present study provide evidence for the application of biological organic fertilizer in the agricultural area of China. Bangladesh J. Bot. 50(3): 911-916, 2021 (September) Special